Educational intervention on the smoking consequences in adolescents from Nuevitas - Moraima Martell Martínez; Norki Betancourt Sánchez; Rosabel Lozada Bazain; Edwin Echemendía Reyes; Leydis Suárez Ramos; Bismar Reyes Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: smoking is a social phenomenon that affects all the population sectors indistinctly and represents one of the biggest problems for health authorities. It is considered a universal epidemic and is a heavy burden for the individual, the family and society. Objective: to carry out educational intervention to modify the adolescents' knowledge about the smoking consequences. Methods: an intervention study was carried out in the doctor´s office 21 of the Francisco Peña Peña Polyclinic, in Nuevitas, on 81 adolescents who met the inclusion criteria. Descriptive statistic was used to analyze the results obtained by applying the survey before and after the educational intervention, which contained the following variables: age group, sex, educational level, associated diseases, and knowledge about smoking. Results: male sex and ages 18 to 19 predominated, an age group that also showed the greatest knowledge about the effects of smoking. The pre-university educational level prevailed. The level of knowledge evaluated as good rose from the 49.38% before the intervention to the 80% after it; that of regular fell from the 45.67% to only the 19%; At the end of the intervention, no adolescent was placed in the category of bad. Conclusions: it was possible to modify the knowledge level about the harmful effects of smoking in adolescents, through educational intervention.